2012
DOI: 10.4236/oja.2012.23013
|View full text |Cite
|
Sign up to set email alerts
|

Sound Wave as a Particular Case of the Gravitational Wave

Abstract: It is demonstrated that the universally accepted system of gas-dynamic (hydrodynamic) equations is applicable only to homogeneous (isentropic) media and requires advancement to get applicable to non-homogeneous media. A generalized equation of gravitational wave for adiabatic and ideal media is obtained from advanced system. From this equation, in turn, is obtained an equation of acoustic wave, which is plane and different form the known equation in that the phase speed of the wave in the Earth atmosphere obvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Therefore, these waves have nothing in common with the waves generated as a result of perturbation of gravitational field and can be propagated in vacuum. The equation for linear gravity wave in immovable inhomogeneous medium was first obtained in the paper [9] where it was shown that exactly this equation describes propagation of sound in the Earth atmosphere correctly. Thus, the generally received opinion that the gravitational field does not have any impact on the sound wave was invalidated.…”
Section: Generalized Equation Of Linear Gravitational Wave In Inhomogmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these waves have nothing in common with the waves generated as a result of perturbation of gravitational field and can be propagated in vacuum. The equation for linear gravity wave in immovable inhomogeneous medium was first obtained in the paper [9] where it was shown that exactly this equation describes propagation of sound in the Earth atmosphere correctly. Thus, the generally received opinion that the gravitational field does not have any impact on the sound wave was invalidated.…”
Section: Generalized Equation Of Linear Gravitational Wave In Inhomogmentioning
confidence: 99%
“…In this section we will obtain analogous equation for moving inhomogeneous medium. Let's consider the generalized system of hydrodynamic equations for inhomogeneous medium in gravitational field of the Earth [9] ( ) ( )…”
Section: Generalized Equation Of Linear Gravitational Wave In Inhomogmentioning
confidence: 99%
See 1 more Smart Citation
“…from which the equation for any wave in Earth's gravitational field, including sound wave equation, can be obtained [4]. We will seek for all perturbed quantities in the form ( , , ) = ( ) exp[ ( − )] and take into account that…”
Section: The Correct Theory Of Linear Surface Wavesmentioning
confidence: 99%
“…It appeared that the equation in its current form is fair only for homogeneous medium and as any medium in gravity field is more or less inhomogeneous, it needs to be generalized. The generalized mass conservation equation is obtained in work [4], in the right part of which an additional summand is entered determining the change of density of constant mass, under isobaric change of its volume as a result of temperature variations conditioned by entropy oscillations in inhomogeneous (nonisentropic) medium. When the first summand equals zero, which is the condition for incompressibility of the medium, the second summand remains, equaling isobaric change of its density.…”
Section: Introductionmentioning
confidence: 99%